Avoiding the Radial Paradox: Neuroendovascular Femoral Access Outcomes After Radial Access Adoption. Issue 3 (March 2022) - Wilkinson, D. Andrew; Majmundar, Neil; Catapano, Joshua S.; Cole, Tyler S.; Baranoski, Jacob F.; Hendricks, Benjamin K.; Cavalcanti, Daniel D.; Frederickson, Vance L.; Ducruet, Andrew F.; Albuquerque, Felipe C.
Abstract : BACKGROUND: Transradial access (TRA) for neuroendovascular procedures is increasing in prevalence. The safety benefits of TRA at a patient level may be offset at a population level by a paradoxical increase in transfemoral access (TFA) vascular access site complications (VASCs), the so-called "radial paradox." OBJECTIVE: To study the effect of TRA adoption on TFA performance and outcomes in neuroendovascular procedures. METHODS: Data were collected for all procedures performed over a 10-mo period after radial adoption at a single center. RESULTS: Over the study period, 1084 procedures were performed, including 719 (66.3%) with an intent to treat by TRA and 365 (33.7%) with an intent to treat by TFA. Thirty-two cases (4.4%) crossed over from TRA to TFA, and 2 cases (0.5%) crossed over from TFA to TRA. TFA was performed in older patients (mean [standard deviation] TFA, 63 [15] vs TRA, 56 [16] years) using larger sheath sizes (≥7 French; TFA, 56.2% vs TRA, 2.3%) ( P < .001 for both comparisons). Overall, 29 VASCs occurred (2.7%), including 27 minor (TFA, 4.6% [18/395] vs TRA, 1.3% [9/689], P = .002) and 2 major (TFA, 0.3% [1/395] vs TRA, 0.1% [1/689], P > .99) complications. Independent predictors of VASC included TFA (OR 2.8, 95% confidence interval [CI] 1.1-7.4) and use of dual antiplatelet therapy (OR 4.2, 95% CI 1.6-11.1). CONCLUSION: TFA remains an important access route, despite a predominantly radial paradigm, and is disproportionately used in patients at increased risk for VASCs. TFA proficiency may still be achieved in predominantly radial practices without an increase in femoral complications.